2009
DOI: 10.1111/j.1365-2524.2009.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated care: what does that really mean?

Abstract: The healthcare system in Australia is struggling to meet the healthcare needs of the ageing population. The pressure on health systems to solve these complex problems can create a sense of urgency to find a panacea in concepts such as coordinated care. A common understanding of coordinated care is often assumed when, in reality, the concept is neither clearly defined nor completely understood. The purpose of this review was to examine and identify the attributes of coordinated care to facilitate a shared defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…Of the 26 studies, one [8] was graded as a 2+, 17 studies were graded as 3, (non-analytical studies), and eight were graded as 4 (expert opinion). In addition to the 26 empirical studies, three literature reviews received a rating of 3 [383940]. The remaining eight articles were not considered to have sufficient evidentiary support.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Of the 26 studies, one [8] was graded as a 2+, 17 studies were graded as 3, (non-analytical studies), and eight were graded as 4 (expert opinion). In addition to the 26 empirical studies, three literature reviews received a rating of 3 [383940]. The remaining eight articles were not considered to have sufficient evidentiary support.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Similarly, Ehrlich et al (2009) emphasise the importance of shared understanding of key concepts. The use of different terminology by practitioners to describe the care coordinator should not continue to obscure the importance of the role and associated activities.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6) Gardiner et al (7) identified the specific needs of people with advanced COPD, highlighting their significant symptom burden, specific needs around education and access to specialist and palliative services as well as the significant issues affecting their families. (7) The basis of best practice care for chronic diseases such as COPD is systematic management (8,9) incorporating co-ordinated, multidisciplinary care (10) and the integration of care between the acute and primary care sectors where multiple providers may be involved. (11) However, there are few current models of care that reflect the key elements of best practice COPD care as summarised by Disler et al (12) and which integrate systematic chronic disease management with a palliative approach.…”
Section: What Are the Implications For Practitioners?mentioning
confidence: 99%
“…should approaches be generic or disease based) and what strategies would improve care co-ordination (see Table 1). (10) INSERT BOX 1 and TABLE 1 HERE One care co-ordination strategy for which there is increasing international evidence is the care co-ordinator role, with the UK (18,19) and US (13,20) increasingly using care coordinators to ensure best practice care for people with chronic and complex conditions. There is no consensus on the definition of a care co-ordinator,…”
Section: What Are the Implications For Practitioners?mentioning
confidence: 99%